Sistem Pakar Diagnosis Penyakit Lupus Berbasis Mobile Application Android dengan Metode Certainty Factor (CF) - Febry, Fransiskus; Darussalam, Ucuk; Esti Handayani, Endah Tri (KITA Institut, 2022)
The objectives of this research are; 1) Creating Android software or applications using the Certainty Factor method, and 2) Early diagnosis of a person's indications using the Certainty Factor (CF) method. The research methodology uses interviews, collects information obtained, the next stage is used with the Certainty Method used to calculate the probability value of MD, MB and CF, researchers to display the diagnosis of Lupus, testing techniques using Acceptance Testing techniques. The results of the study have succeeded in making an application using the JAVA programming language assisted by the Android SDK Platform. The results of the disease obtained a confidence value indication of Dry Eyes, Shortness of Breath due to Lung Inflammation, Continuous Chest Pain for Lupus is 0.968815.